Scale of competencies for sustainability at the organizational scope - Garlet, Valéria; Beuron, Thiago Antônio; Ávila, Lucas Veiga; Balsan, Laércio André Gassen; Madruga, Lúcia Rejane da Rosa Gama; Kraetzig, Elda Rodrigues Steinhorst (Revista de Administração da UFSM, 2024)
Objective: The objective of the study is to propose an instrument to evaluate the Competencies for Sustainability in Organizations. Originality/Value: The importance of sustainability is clearly evidenced in the proposition of the Sustainable Development Goals (SDGs). The skills for sustainability portray the commitment to sustainability. Understanding and effectively evaluating this set of skills is important to face the problems of society and the planet in terms of the environment, economy, and culture, among others, through conscious and sustainable decision making. For there to be a more sustainable world, it is necessary to understand that all obligors are agents of change endowed with skills that drive them to act and to change. What are the competencies needed for sustainability? By making available an instrument that aims to identify competencies that promote sustainability, it is intended to expand the scientific discussion on relevant issues that can influence society and help in the construction of a more sustainable future. Design/methodology/approach: The items were compiled on the instrument based on the literature. After analyzing the content of the items, analyzing the specialists, semantic analysis, and pretesting the preliminary version of the instrument was applied to a sample of 509 respondents. Results: A factor analysis was carried out that revealed two factors: strategic planning for sustainability and valuing sustainability. Together, the two factors explained 61.15% of the total variance of the construct. The 10 items have constitutive and operational consistency, and the results demonstrated the construct’s validity with good reliability indexes, good factorial load, and good model adjustment indexes.